2020
DOI: 10.33448/rsd-v9i9.7932
|View full text |Cite
|
Sign up to set email alerts
|

Non-clinical safety study of a sugarcane bacterial cellulose hydrogel

Abstract: A hydrogel of bacterial cellulose of 0.8%, biopolymer produced from sugarcane molasses and synthesized from a bacteria called Zoogloea sp., was analyzed for its composition and tested by two routes of administration, subcutaneous and intraperitoneal, to clarify the local and systemic adverse effects after skin implantation in Wistar rats (24 males, 24 females, 55 days old). Analysis of two samples of BC films indicates carbon (42.94%; 43.43%), hydrogen (6.73%; 6.76%), nitrogen (0.28%, 0.23%) and oxygen (50.05%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Moreover, it is important to highlight that the hydrogel developed by Zoogloea sp. has undergone comprehensive evaluation in toxicity tests, as described by Pinto et al [34], and safety studies conducted by Silva et al [24]. Clinical research led by Silva et al [26] confirmed not only the safety of the product but also its high capacity to promote wound healing in chronic venous ulcers in the lower extremities, showing significant reductions in wound area, improved healing rates, and positive patient outcomes when compared to standard dressings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is important to highlight that the hydrogel developed by Zoogloea sp. has undergone comprehensive evaluation in toxicity tests, as described by Pinto et al [34], and safety studies conducted by Silva et al [24]. Clinical research led by Silva et al [26] confirmed not only the safety of the product but also its high capacity to promote wound healing in chronic venous ulcers in the lower extremities, showing significant reductions in wound area, improved healing rates, and positive patient outcomes when compared to standard dressings.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of hydrogel is similar to the extract of an extracellular matrix and soft tissues, which presents a distinct three-dimensional conformation of nanofibrils and microfibrils that enables the adhesion of compounds due to the hydroxyl groups that make up its surface [19][20][21][22]. A hydrogel produced from sugar cane molasses has been tested in different medical and biomedical areas, showing promising results, including stability due to sugar polymerization, low toxicity, biocompatibility, and efficiency for tissue remodeling [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Na avaliação de biomateriais para dispositivos médicos, testes em animais são procedimentos inerentes para estimar a biocompatibilidade de um novo biomaterial antes do seu uso clínico de modo que sejam verificados efeitos tóxicos, sistêmicos e locais. A toxicidade in vivo pode ser avaliada por sinais clínicos e testes laboratoriais de hematologia, bioquímica sérica, avaliação de tecidos e órgãos, análise histopatológica, e investigação de reação inflamatória (ISO 10993, 2010) Os estudos pré-clínicos, in vivo, desenvolvidos com a CB investigaram a reatividade cutânea (Lucena et al, 2015), a bicompatibilidade e reação de sensibilidade local (Pita et al, 2015), a citotoxicidade e potencial genotóxico (Pinto et al, 2015) e os efeitos adversos locais e sistêmicos (Silva et al, 2020). Nestes estudos foram usados como parâmetros avaliativos sinais clínicos, atividade enzimática, resposta inflamatória, tempo de cicatrização, análise histopatológica e reatividade cutânea/subcutânea frente a aplicação da CB na apresentação de membrana e hidrogel a 0,8% (em animais domésticos e roedores).…”
Section: Biocompatibilidade Da Celulose Bacterianaunclassified